The Impact Of Corporate Social Irresponsibility On Workplace Deviant Behaviours Of Non- Managerial Employees: A Cross Generational Study Of Pakistan - Ahmed, Munir (2022)
Workplace deviant behaviours pose a serious challenge to organizational performance as more the 30% of businesses failures are attributed to workplace deviant behaviours. To investigate whether there is association between corporate social irresponsibility and workplace deviant behaviours, this study developed a theoretical framework under the attribution theory by integrating internal and external corporate social irresponsibility, personal anger, moral outrage, organizational and interpersonal workplace deviant behaviours in three different groups of generations, namely X, Y, and Z. The data was collected from a sample of 327 non-managerial employees selected through purposive sampling from 20 firms of power distribution, petroleum, refinery, and banking industry of Pakistan. The model was assessed by employing multigroup analysis of PLS-SEM. The findings suggested that internal corporate social irresponsibility has positive effect on organizational and interpersonal workplace deviant behaviours. This effect was observed higher in generation Z, followed by generation Y and generation X. On the other hand, external corporate social irresponsibility has a positive impact only on organizational workplace deviant behaviours. Personal anger mediated positively between internal corporate social irresponsive and organizational & interpersonal workplace deviant behaviours, whereas moral outrage is a significant mediator between external corporate social irresponsibility and organizational workplace deviant behaviour only.